Integration of approaches in combatting terrorism financing: identifying the sources - Zul Kepli, Mohd Yazid; Malik, Maszlee; Mohd Yasin, Norhashimah (2018)
This paper attempts to clarify and describe the sources of terrorism financing and the perpetrators who finance them. This paper is based on the content analysis of mutual evaluation reports, leading textbooks, journal articles and newspaper reports. It also benefited from the interviews with leading officers from the police force and the special unit on anti-terrorism, and academicians. The discussion covers the classification of terrorism activities and the related costs. The paper also analyzes and compares the size and type of financing available to terrorists and draws conclusions on the general characteristics of these threats. How terrorists move money, and how this can be disrupted, is also covered. Analysis on common mistakes in combatting terrorism is also included, and this paper ends with suggestions and recommendations on how to combat terrorism financing properly. The paper also emphasizes the importance of combatting all type of terrorism financing using integrated approach, instead of selectively.